Usp9X Regulates Cell Death in Malignant Peripheral Nerve Sheath Tumors. Issue 1 (December 2018) - Bianchetti, E.; Bates, S.; Carroll, S.; Siegelin, M.; Roth, K.
Abstract Malignant peripheral nerve sheath tumors (MPNSTs) are the leading cause of death in neurofibromatosis type 1 (NF1) patients. Current treatment modalities have been largely unsuccessful in improving MPNST patient survival, making the identification of new therapeutic targets urgent. In this study, we found that interference with Usp9X, a deubiquitinating enzyme which is overexpressed in nervous system tumors, or Mcl-1, an anti-apoptotic member of the Bcl-2 family whose degradation is regulated by Usp9X, causes rapid death in human MPNST cell lines. Although both Usp9X and Mcl-1 knockdown elicited some features of apoptosis, broad spectrum caspase inhibition was ineffective in preventing knockdown-induced MPNST cell death suggesting that caspase-independent death pathways were also activated. Ultrastructural examination of MPNST cells following either Usp9X interference or pharmacological inhibition showed extensive cytoplasmic vacuolization and swelling of endoplasmic reticulum (ER) and mitochondria most consistent with paraptotic cell death. Finally, the Usp9X pharmacological inhibitor WP1130 significantly reduced human MPNST growth and induced tumor cell death in anin vivo xenograft model. In total, these findings indicate that Usp9X and Mcl-1 play significant roles in maintaining human MPNST cell viability and that pharmacological inhibition of Usp9X deubiquitinase activity could be a therapeutic target for MPNST treatment.